2020
DOI: 10.3390/toxics8030062
|View full text |Cite
|
Sign up to set email alerts
|

Use of Personal Care Products and Semen Quality: A Cross-Sectional Study in Young Danish Men

Abstract: Personal care products (PCPs) may contain multiple chemicals capable of harming male reproductive function. The aim of this study was, therefore, to assess aggregated PCP exposure and potential associations with measures of semen quality in young men. Participants (n = 1058, age 18–21) were sampled among young men from the Danish National Birth Cohort (DNBC). Upon recruitment in 2017–2019, each man answered an online questionnaire and provided a semen sample. Exposure to 12 common types of PCPs was derived fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 42 publications
(85 reference statements)
0
7
0
Order By: Relevance
“…Forty‐six papers were published in the 2000–2013 period (selected from the review of Levine et al.) and further 19 papers were identified during the period 2014–2020 22–40 (Figure 1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Forty‐six papers were published in the 2000–2013 period (selected from the review of Levine et al.) and further 19 papers were identified during the period 2014–2020 22–40 (Figure 1).…”
Section: Resultsmentioning
confidence: 99%
“…Two authors reviewed the papers and independently selected the articles eligible for systematic review, and discrepancies were resolved by discussion. Then, we selected 19 papers 22–40 published in the 2000–2013 period. As regards the articles published in the 2000–2013 period, we identified 46 papers from the review by Levine et al.…”
Section: Methodsmentioning
confidence: 99%
“…The psychological, social, and economic consequences of reduced male capacity to have children are often severe and extend beyond individuals to entire families and society at large. The previously discussed subject of decline in male fertility is no longer controversial because many studies over the past 10 years have shown a decrease in semen quality [4,[17][18][19]. EDCs affect the maturation, function, and viability of sperm by acting directly on the sperm or altering the function of the epididymis as well as the sperm's ability to fertilize an egg.…”
Section: Male Infertilitymentioning
confidence: 99%
“…These products contain many components such as phthalates, parabens, UV filters, polycylic musks, antimicrobials, formaldehyde, which are used different purposes. In addition, many cosmetic products contain heavy metals such as lead, cadmium, antimony, chromium, arsenic, mercury, nickel as ingredient or impurities [18,67]. The main route of exposure is through the skin and through inhalation.…”
Section: Cosmetics (Uv Filters)mentioning
confidence: 99%
See 1 more Smart Citation